2008
DOI: 10.1074/jbc.m806755200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of MutS2 Endonuclease Domain and the Mechanism of Homologous Recombination Suppression

Abstract: DNA recombination events need to be strictly regulated, because an increase in the recombinational frequency causes unfavorable alteration of genetic information. Recent studies revealed the existence of a novel anti-recombination enzyme, MutS2. However, the mechanism by which MutS2 inhibits homologous recombination has been unknown. Previously, we found that Thermus thermophilus MutS2 (ttMutS2) harbors an endonuclease activity and that this activity is confined to the C-terminal domain, whose amino acid seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 54 publications
3
72
1
Order By: Relevance
“…To our knowledge, our observation of MMC sensitivity is the first phenotype shown for a ΔmutS2 deletion in B. subtilis. A previous study of Thermus thermophilus mutS2 found that deletion of mutS2 resulted in resistance to MMC treatment relative to the wild type, consistent with the inhibitory effect of TtMutS2 on recombination (22). Given that deletion of B. subtilis mutS2 has the opposite effect of TtΔmutS2, these results suggest that B. subtilis MutS2 promotes homologous recombination, a novel result for a bacterial MutS2 protein.…”
supporting
confidence: 54%
See 3 more Smart Citations
“…To our knowledge, our observation of MMC sensitivity is the first phenotype shown for a ΔmutS2 deletion in B. subtilis. A previous study of Thermus thermophilus mutS2 found that deletion of mutS2 resulted in resistance to MMC treatment relative to the wild type, consistent with the inhibitory effect of TtMutS2 on recombination (22). Given that deletion of B. subtilis mutS2 has the opposite effect of TtΔmutS2, these results suggest that B. subtilis MutS2 promotes homologous recombination, a novel result for a bacterial MutS2 protein.…”
supporting
confidence: 54%
“…The function of B. subtilis MutS2 (BsMutS2) in genome maintenance is unknown. We initially hypothesized that B. subtilis MutS2 participated in antirecombination, as demonstrated for H. pylori and T. thermophilus MutS2 (19,22). Instead, here we report that MutS2 promotes homologous recombination in B. subtilis.…”
mentioning
confidence: 63%
See 2 more Smart Citations
“…In this study, we use the following naming of the MutS subfamilies, which is adapted from the recent study by Lin et al (Lin et al, 2007). In total, 12 subfamilies were previously described to compose the MutS family: 'MutS1/ MSH1' including E. coli MutS and the mitochondria-targeted fungal MutS homolog 1 (MSH1); 'MutS2', known to inhibit recombination in H. pylori (Pinto et al, 2005) and to possess a C-terminal endonuclease domain called the small MutS-related (Smr) domain (Moreira and Philippe, 1999;Fukui et al, 2008); 'MSH2', 'MSH3', 'MSH4', 'MSH5' and 'MSH6/7', found in most eukaryotes (with the exception of MSH7 being a plant-specific paralogous group of MSH6 (Wu et al, 2003)); another plantspecific MSH1 (called 'plt-MSH1' hereafter) with the GIY-YIG endonuclease domain at their C-terminus (Abdelnoor et al, 2006); 'MutS3', 'MutS4' and 'MutS5', recently described but functionally uncharacterized prokaryotic homologs (Lin et al, 2007), and the above mentioned 'MutS7' subfamily represented by the Mimivirus MutS homolog.…”
Section: Introductionmentioning
confidence: 99%